THE POWER OF EMBODIED AND ARTS-BASED LEARNING IN THE SHARED HUMANITY EXPERIENTIAL LEARNING INITIATIVE AT STELLENBOSCH UNIVERSITY. - Costandius, E.; Pryde, S.; Andrews, R. (South African Journal of Higher Education, 2025)
The transformation of higher education in South Africa has tended to focus on issues such as access and representation, leaving curricula insufficiently addressed. This is surprising, considering that much previous scholarship, including the recent Khampepe Report, has called for the implementation of a specific pedagogical framework to foster in students critical and holistic perspectives about social justice issues and dismantle pre-existing biases. Shared Humanity: Lessons in Critical Thinking at Stellenbosch University was designed with these issues in mind and was implemented in 2019 as a pilot by the Division: Student Affairs in the Unit for Experiential Learning. This article discusses the visual arts session of Shared Humanity, which is premised on relational perspectives derived from post-empirical and indigenous knowledge frameworks. By examining relevant literature, specific learning practices and students’ reflections from the visual arts session, the article makes a case for the meaningful inclusion and development of embodied and arts-based learning strategies in social justice pedagogical frameworks in higher education. It argues that embodied and arts-based learning strategies offer new ways of thinking and learning about old problems, and, as such, can become powerful tools for engaging students meaningfully in the transformation project. This article, therefore, focuses on student experiences of arts-based embodied methods to enhance teaching and learning related to social justice concerns.